1st REPS research colloquium - The Ad-Hoc Committee of REPS UP NISMED auditorium; De Ungria, Maria Corazon A. University Researcher III, College of Science, Natural Science and Research InstitutePhilosophy; Arlante, Salvacion M. University Librarian, UP Diliman; Tan, Merle C. Director, UP NISMED; Cordero, Rosa R. University Research III, UP National College of Public Administration and Governance; Disierto, Diane A. Law Reform Specialist, UP College of Law.; University of the Philippines (Diliman). UP NISMED Auditorium; 1st REPS Research Colloquium (Quezon City University of the Philippines Diliman, 2008)
The Research, Extension and Professional Staff (REPS) of the University of the Philippines, Diliman gathered last February 22, 2008 at the UP National Institute for Science and Mathematics Education Development (UP NISMED) for the 1st REPS Research Colloquium conducted by the Ad-Hoc Committee of REPS with the support of the Office of the Chancellor. This colloquium presented notable research by REPS who have contributed to policy formulation and capability building of human resources. The event also served as a venue for the academic community to discuss the current issues confronting Philippine society in general and the University?s response to these issues.
Disc 1: Opening ceremony; Introduction of the speaker; Opening Remarks / Chancellor Sergio S. Cao (1 hr. 02 min. 36 sec.) -- Disc 2. Impact of DNA evidence in the Philippine criminal justice system / Maria Corazon A. De Ungria (49 min. 23 sec.) -- Disc 3: The UP iLib : an in-house developed integrated library system / Salvacion M. Arlante (1 hr. : 36 sec.).-- Disc: Raising the quality of science and mathematics education : lessons from ground level / Merle C. Tan; Motivating success in GIS development through effective change management / Rosa R. Cordero ( 58 min. : 29 sec.) --Disc 5: The contours of command responsibility : Philippine incorporation and customary evolution / Diane A. Disierto; Industry clustering : inspiring ways to competitiveness / Sonia Tiong-Aquino (59 min. : 52 sec.)-- Disc 6: Brainstorming session (44 min. : 59 sec.)
DVD.
Introducer: Malaya Ronas.
Keywords: Policy formulation -- Human Resources -- Research